2008
DOI: 10.17221/347-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of five Chinese goat breeds assessed by microsatellite markers

Abstract: ABSTRACT:The genetic diversity was studied using microsatellite DNA markers in Laoshan dairy goat (LS), Xinong Saanen dairy goat (SN), Guanzhong dairy goat (GZ), Banjiao goat (BJ) and Guizhou white goat (GW). Within the nine polymorphic loci, allele frequencies, number of effective alleles (Ne), heterozygosity (He), polymorphism information content (PIC), genetic identity (I) and Nei's standard genetic distance (D) were calculated, and UPGMA phylogenetic tree was constructed based on allele frequencies. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
3
12
1
3
Order By: Relevance
“…In the present study, about 81% of the loci showed positive deviation from Hardy-Weingberg equilibrium. The mean observed and expected heterozygosities obtained in this study is higher than that reported in other goat breeds [5,12,16]. The fairly high value of inbreeding estimate (F IS ) indicated that some of the loci in this breed were homozygous presumably resulting from the mating between relatives and consequent genetic drift.…”
Section: Resultscontrasting
confidence: 67%
“…In the present study, about 81% of the loci showed positive deviation from Hardy-Weingberg equilibrium. The mean observed and expected heterozygosities obtained in this study is higher than that reported in other goat breeds [5,12,16]. The fairly high value of inbreeding estimate (F IS ) indicated that some of the loci in this breed were homozygous presumably resulting from the mating between relatives and consequent genetic drift.…”
Section: Resultscontrasting
confidence: 67%
“…Comprehensive knowledge of genetic diversity is the first step for conservation of a given population (LI et al 2008). The results of the present work indicate a similarity of the subpopulations.…”
Section: Microsatellite Markerssupporting
confidence: 56%
“…Moradii et al (2014) showed that the phylogenetic dendrogram of color types using ISSR markers was in agreement with their phenotypic similarities, in which saddle brown and sandy brown color types were grouped in one cluster and black types in another one. However, the current study is the first report using ISSR marker analysis to investigate the possibility of different clustering for the twining trait in several goat populations (Agha et al, 2008;Dixit et al, 2012;Javanrouh Aliabad et al, 2004;Li et al, 2008;Mirhoseini and Badbarin, 2013).…”
Section: Discussionmentioning
confidence: 96%